Copied from the collection of: Süddeutscher Verlag, Stuttgart: the treason-trial at Leipzig against Liebknecht, Hepner and Bebel (at the right)
Copied from the collection of: Süddeutscher Verlag, Stuttgart: the treason-trial at Leipzig against Liebknecht, Hepner and Bebel (at the right).